A Service Evaluation Exploring Referrals Made From Primary Care to CAMHS in Children With a Potential Diagnosis of ADHD, Autism and Other Mental Health Conditions in a South London Based GP Practice - Thusani Nanthakumaran (BJPsych Open)
Aims: This service evaluation aims to identify and assess referrals made to CAMHS at a south London based GP practice. The focus of this evaluation will be on referrals for Attention Deficit hyperactivity Disorder (ADHD), autism, anxiety and other mental health conditions such as depression and suicidal ideation. It will also aim to assess if the support available to parents and children is sufficient and if the long waiting times creates pressure on the practice.